On Farm Testing of Rice Residue Management Techniques for Wheat (Triticum aestivum L.) Establishment in Punjab (Indian Journal of Extension Education, 2021)
Rice residue management (RRM) has been the key component of systems’ sustainability. The paper reports the effect of different RRM and wheat (Triticum aestivum L.) establishment methods on productivity and yield contributing attributes through farmer participatory mode in south-western Punjab. Different RRM technologies including rice residue removal, residue incorporation and residue retention on soil as surface mulch were evaluated. Wheat grain yield was significantly (p<0.05) higher with happy seeder method of wheat establishment following chopping of loose rice stubble, which acts as surface mulch, compared with the other RRM technologies. Wheat grain yield in other RRM technologies viz. rice residue incorporation and removal did not differ significantly. The yield contributing attributes viz. plant height, number of effective tillers m-1 row length, 1000-grain weight, ear length and the number of grains ear-1 were significantly higher in happy seeder method of wheat establishment. The weed count (Phalaris minor) was significantly lower than the other compared methods of RRM. The correlation matrix exhibited a linear positive relationship between the grain yield and plant height (r=0.951*; p<0.05), ear length (r=0.941*), 1000-grain weight (r=0.853*) and number of grains ear-1 (r=0.771*). All economic indices viz. average net (Rs. 74, 840/- ha-1), gross returns (Rs. 1,00,620/- ha-1) and benefit-cost (B:C; 3.9) ratio were significantly enhanced because of low cost of cultivation (Rs. 25,780/- ha-1) under happy seeder method of wheat establishment.